Influence of Smoking and Paprika Spice on the Content of Polycyclic Aromatic Hydrocarbons (PAHs) in the Traditional Spanish Smoked Sausage ‘Botillo del Bierzo’ - Jaime R. Fuertes-Martínez; Marcos Guerra; Álvaro Rodríguez-González; Héctor del Valle-Herrero; José B. Valenciano; Víctor Marcelo (Foods)
The content of polycyclic aromatic hydrocarbons (PAHs) in a traditional Spanish smoked sausage known as ‘Botillo del Bierzo’ was analysed. The determination and quantification of PAH4 (the sum of benzo[a]pyrene, benz[a]anthracene, benzo[b]-fluoranthene and chrysene) in the smoked sausage were performed using GC–MS. The results showed that smoking ‘Botillo del Bierzo’ for 24 h contributes very little to the increase in PAH levels in the product, with no significant differences (p < 0.05). The paprika used in the production of botillo also contributes to PAH content, depending on the paprika’s production process (smoked, low-smoked, mixed paprika (smoked + unsmoked or low-smoked + unsmoked), and unsmoked), with significant differences among them (p < 0.05). Using paprika with a lower PAH content (unsmoked or mixed) enables the production of ‘Botillo del Bierzo’, in accordance with Protected Geographical Indication specifications, with a lower PAH content while maintaining the organoleptic characteristics provided by the paprika. The contamination levels detected in ‘Botillo del Bierzo’ do not pose a risk to consumer health, as the benzo[a]pyrene and PAH4 values are well below the regulatory limits of 5 μg/kg and 30 μg/kg, respectively.